Experimental quantification of solar panel power activation delay post-illumination with metrological analysis - Sedelnikov, Andry; Marshalkina, Alexandra; Evtushenko, Maksim (Edelweiss Applied Science and Technology, 2025)
The issue of solar panel power activation delay is significant when modeling processes that change rapidly. This assessment enables the correct decision to either neglect the generated electrical power if it is minimal or to include it in the model. Resolving this issue experimentally is often the most straightforward approach due to the considerable nonlinearity of transient electrical processes, which requires the development of complex mathematical models. The primary objective of this research is to experimentally estimate the delay time for solar panel power activation. The methodology involves direct measurements of the voltage produced by the solar panel. A metrological model of the experiment has been developed, allowing for the estimation of errors in the measurement of the solar panel's turn-on delay time. Experiments were conducted using three solar panels from different manufacturers. The results obtained are slightly lower than the values provided on the manufacturers' official websites. The methodology and metrological model presented can be utilized to accurately simulate the temperature shock experienced by spacecraft solar panels.